2012
DOI: 10.1021/mz200219y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Localized Network Damage in Block Copolymer Toughened Epoxies

Abstract: The underlying mechanisms responsible for the toughening of block copolymer modified thermoset epoxies are not completely understood. A current theory targets cavitation of the rubbery cores in dispersed micelles as the key event that triggers shear yielding, resulting in enhanced toughness. To evaluate this hypothesis, we prepared spherical micelle forming block copolymers with rubbery cores (prone to cavitation) and glassy cores (unable to cavitate). Surprisingly, both systems enhance fracture toughness, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 36 publications
4
74
0
Order By: Relevance
“…13 Recent simultaneous deformation and scattering experiments have confirmed the two relevant ideas for our discussion: cavitation in rubbery nanodomains and lack of void formation in epoxies modified with glassy core micelles. 14 However, in a previous paper 18 we reported that micelle core cavitation is not a necessary condition for toughening, as glassy core micelles also toughened epoxies, despite their inability to cavitate. It is important to note that the origins of toughness in epoxies modified with glassy core micelles are fundamentally different from the toughening mechanism in epoxies modified with other rigid particles.…”
Section: Toughening Mechanismmentioning
confidence: 90%
See 2 more Smart Citations
“…13 Recent simultaneous deformation and scattering experiments have confirmed the two relevant ideas for our discussion: cavitation in rubbery nanodomains and lack of void formation in epoxies modified with glassy core micelles. 14 However, in a previous paper 18 we reported that micelle core cavitation is not a necessary condition for toughening, as glassy core micelles also toughened epoxies, despite their inability to cavitate. It is important to note that the origins of toughness in epoxies modified with glassy core micelles are fundamentally different from the toughening mechanism in epoxies modified with other rigid particles.…”
Section: Toughening Mechanismmentioning
confidence: 90%
“…18 This paper expands upon that work by better understanding the differences in spherical micelle core composition and additive concentration on the toughening of epoxy thermosets. In particular, the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 effect of PEO homopolymer addition on microstructure and mechanical properties of the epoxy matrix is studied to provide insight to the corona, and fractographic analysis is carried out to explore further the differences between the fracture behavior of epoxies modified by glassy and rubbery cores.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…When high levels of the rubbery phase are required, rubber toughening may also result in materials with reduced modulus, lower glass transition temperatures and increased resin viscosities. 18 Diblock copolymer toughening of epoxy resins 23 enables toughening of thermoset systems without significant sacrifices in the modulus or glass transition temperature. 24 Further, by altering diblock copolymer structure by manipulating the chain segment block lengths, the toughening characteristics of the resulting thermoset materials can be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Block copolymer (BCP)/epoxy blends have been the subject of a large number of recent studies where the focus was placed on the role of the BCP as a processing aid [1,2], as a template for the self-assembly of different type of nanoparticles [3][4][5], or as a toughening agent [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The nanostructuration of the BCP in the epoxy matrix requires an immiscible block, either initially [20,21] or during polymerization [22,23], and another block that keeps its miscibility up to high or full conversions.…”
Section: Introductionmentioning
confidence: 99%